Hierarki Pengaruh dalam Kebijakan Redaksi MetroTV: Studi Kasus Pemberitaan Pilpres 2024 - Pediati, Lia; Zahra, Aida Farida; Fairus, Muhammad Khubbab; Jamaludin, Amal; Lubis, Muhammad Haidar Pasya; Heryanto, Gun Gun (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The relationship between the media and political actors will be seen from the intensity of the coverage, the closeness that has the potential to give birth to exclusivity, the availability of more opportunities for media coverage. This is difficult to ignore in the era of democratic parties. Political actors and the media may have a special relationship that can influence the news. As we know, MetroTV and Surya Paloh are two inseparable things. This research aims to analyze the hierarchy of influence in MetroTV's editorial policy on the coverage of the 2024 presidential election. This research uses a descriptive qualitative approach, taking primary data from interviews and documentation, as well as secondary data from literature that has relevance to this research. Researchers have found three hierarchical levels of influence that affect MetroTV's editorial policy, namely the organization level, media routine level and extra media level. In addition, MetroTV's ideology of national principles and knowledge to elevate is not strong enough to influence the editorial policy of the 2024 presidential election news on MetroTV